2005
DOI: 10.1063/1.2074967
|View full text |Cite
|
Sign up to set email alerts
|

Quantum diffusion in liquid water from ring polymer molecular dynamics

Abstract: We have used the ring polymer molecular-dynamics method to study the translational and orientational motions in an extended simple point charge model of liquid water under ambient conditions. We find, in agreement with previous studies, that quantum-mechanical effects increase the self-diffusion coefficient D and decrease the relaxation times around the principal axes of the water molecule by a factor of around 1.5. These results are consistent with a simple Stokes-Einstein picture of the molecular motion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
194
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(203 citation statements)
references
References 55 publications
4
194
4
1
Order By: Relevance
“…Two widely used methods based on imaginary-time path integrals are centroid molecular dynamics (CMD) [24][25][26][27][28] and ring-polymer molecular dynamics (RPMD). [29][30][31][32] Although both methods have known artifacts, such as the spurious-mode effect in RPMD [33][34][35] and the curvature problem 35,36 in CMD, they have proven effective for a vast range of chemical applications including the calculation of thermal rate constants, 30,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] diffusion coefficients, 31,[56][57][58][59][60][61] and vibrational spectra. [33][34][35][36][62][63][64]…”
Section: Introductionmentioning
confidence: 99%
“…Two widely used methods based on imaginary-time path integrals are centroid molecular dynamics (CMD) [24][25][26][27][28] and ring-polymer molecular dynamics (RPMD). [29][30][31][32] Although both methods have known artifacts, such as the spurious-mode effect in RPMD [33][34][35] and the curvature problem 35,36 in CMD, they have proven effective for a vast range of chemical applications including the calculation of thermal rate constants, 30,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] diffusion coefficients, 31,[56][57][58][59][60][61] and vibrational spectra. [33][34][35][36][62][63][64]…”
Section: Introductionmentioning
confidence: 99%
“…Static properties can be calculated exactly using this mapping while RPMD uses the classical evolution of the polymers to provide an approximation to quantum dynamics. This approach has been previously shown to give accurate dynamical properties for systems ranging from nearly classical to those where tunnelling is dominant 21,22 .…”
mentioning
confidence: 99%
“…Habershon et al 84 showed that the ring polymer molecular dynamics (RPMD) model [85][86][87][88][89][90][91]92 could provide a good 'prior' for the MEAC. LSC-IVR, RPMD, and the centroid molecular dynamics [93][94][95][96][97][98][99][100][101][102][103][104][105] (CMD) are all approximate ways for adding some quantum effects to classical MD simulations, though none of them incorporate 'true' quantum coherence effects.…”
Section: ˆ/ Iht E −mentioning
confidence: 99%